The Phyto-Oestrogens - Its Anticarcinogenic and Antioxidant Activity - A Review - Sitarina Widyarini (Indonesian Food and Nutrition Progress, 2005)
The isoflavonoids comprise a group of phytooestrogens that have useful biological activities including oestrogenic, antioxidant and anticancer. As dietary components for humans, they are bioavailable from leguminous vegetables (such as genistein from soybean), and have been well-documented to have numerous health benefits. A wide range of epidemiological studies in humans and limited studies in animals have identified isoflavonoids as a potential chemopreventive agents against hormone-dependent cancers. Therefore, this review focuses on the mechanisms of isoflavonoid phyto-oestrogens in inhibiting cancer in vitro and in vivo in the models of human cancers.